Combined p14ARF and Interferon-β Gene Transfer to the Human Melanoma Cell Line SK-MEL-147 Promotes Oncolysis and Immune Activation - Cerqueira, Otto Luiz Dutra; Clavijo-Salomon, Maria Alejandra; Cardoso, Elaine Cristina; Citrangulo Tortelli Junior, Tharcisio; Mendonça, Samir Andrade; Barbuto, José Alexandre M.; Strauss, Bryan E. (Frontiers in Immunology, 2020)
Immune evasion is an important cancer hallmark and the understanding of its mechanisms has generated successful therapeutic approaches. Induction of immunogenic cell death (ICD) is expected to attract immune cell populations that promote innate and adaptive immune responses. Here, we present a critical advance for our adenovirus-mediated gene therapy approach, where the combined p14ARF and human interferon-β (IFNβ) gene transfer to human melanoma cells led to oncolysis, ICD and subsequent activation of immune cells. Our results indicate that IFNβ alone or in combination with p14ARF was able to induce massive cell death in the human melanoma cell line SK-MEL-147, though caspase 3/7 activation was not essential. In situ gene therapy of s.c. SK-MEL-147 tumors in Nod-Scid mice revealed inhibition of tumor growth and increased survival in response to IFNβ alone or in combination with p14ARF. Emission of critical markers of ICD (exposition of calreticulin, secretion of ATP and IFNβ) was stronger when cells were treated with combined p14ARF and IFNβ gene transfer. Co-culture of previously transduced SK-MEL-147 cells with monocyte-derived dendritic cells (Mo-DCs) derived from healthy donors resulted in increased levels of activation markers HLA-DR, CD80 and CD86. Activated Mo-DCs where able to prime autologous and allogeneic T cells, resulting in increased secretion of IFNγ, TNF-α and IL-10. Preliminary data showed that T cells primed by Mo-DCs activated with p14ARF+IFNβ-transduced SK-MEL-147 cells were able to induce the loss of viability of fresh non-transduced SK-MEL-147 cells, suggesting the induction of a specific cytotoxic population that recognized and killed SK-MEL-147 cells. Collectively, our results indicate that p14ARF and IFNβ delivered by our adenoviral system induced oncolysis in human melanoma cells accompanied by adaptive immune response activation and regulation.